2018
DOI: 10.1111/ijag.12346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deposition conditions on physical properties of sputtered silicon oxynitride thin films on float glass

Abstract: Silicon oxynitride layers have been widely used to tailor the optical performance and mechanical resistance of multilayer optical coatings. The key issue for their reliable large‐scale application on a glass substrate is the effect of technological parameters on their performance. Here we report on the interrelationship between the conditions of the reactive magnetron deposition process and composition, structure and in turn optical and mechanical properties. The process gas composition and pressure level exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Optical coating systems represent a particular challenge since their design must not compromise their functional properties and coating deposition must be performed at temperatures low enough not to degrade the glass substrate. Optimising their mechanical properties to improve their durability will be critical if they are to be used successfully in harsh environments where they may be subject to mechanical contact [11][12][13][14][15][16]. Improving resistance to damage by retaining some level of elasticity along with hardness should improve performance on duplex coatings, for example, for mirror systems.…”
Section: And Co-workersmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical coating systems represent a particular challenge since their design must not compromise their functional properties and coating deposition must be performed at temperatures low enough not to degrade the glass substrate. Optimising their mechanical properties to improve their durability will be critical if they are to be used successfully in harsh environments where they may be subject to mechanical contact [11][12][13][14][15][16]. Improving resistance to damage by retaining some level of elasticity along with hardness should improve performance on duplex coatings, for example, for mirror systems.…”
Section: And Co-workersmentioning
confidence: 99%
“…Small scale testing provides a convenient route to optimisation. For example, ramped load scratch tests have been used to assess fracture strength [15] and repetitive nano-scratch (low cycle nano-wear) tests have been used to simulate abrasion [11][12]. Nano-wear tests on amorphous silica and silicon oxynitride thin films deposited by reactive RF magnetron sputtering on soda lime float glass have shown that their scratch resistance can be tailored by optimising the deposition conditions [11][12].…”
Section: And Co-workersmentioning
confidence: 99%
“…When the SiN x O y film is applied to the anti-reflection coating, the hardness of the coating is greatly improved. Additionally, Simurka et al [100] deposited a SiN x O y film on a glass substrate by pulsed DC magnetron sputtering with a constant flow of Ar (38–94 sccm) as the working gas and a constant gas flow ratio of oxygen (2–5 sccm) and nitrogen (20 sccm) is employed. Through experimental characterizations, it is found that as the sputtering power increases, the density, refractive index, hardness, and Young’s modulus of the film increase slightly.…”
Section: Preparation Of Sinxoy Filmmentioning
confidence: 99%
“…1 With structure and properties transitioning from stoichiometric silica (SiO 2 ) to silicon nitride (Si 3 N 4 ), 2 amorphous SiO x N y films have been widely used in the fields of micro-and optoelectronics. 3 They have especially garnered attention since the early 2000s as high-k replacements for the classical SiO 2 gate dielectrics. 4 Their denser network in comparison to SiO 2 lends them promising scratch-resisting, encapsulation, anticorrosion, and ion diffusion-limiting properties, finding them a spot in applications such as Na and B diffusion barriers in light emitting devices (LED), 5 acoustic wave devices, 6 at the TiO 2 /SiON/n-Si gate-stacks for advanced CMOS devices, 7 and for hard encapsulation of carbon dots.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Silicon oxynitride (SiO x N y ) films have gathered increasing attention in international technology policy concepts such as the recent Key Enabling Technologies of the European Union . With structure and properties transitioning from stoichiometric silica (SiO 2 ) to silicon nitride (Si 3 N 4 ), amorphous SiO x N y films have been widely used in the fields of micro- and optoelectronics . They have especially garnered attention since the early 2000s as high-k replacements for the classical SiO 2 gate dielectrics .…”
Section: Introductionmentioning
confidence: 99%